2010
DOI: 10.1111/j.1464-410x.2010.09786.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma: stage, grade and histology migration over the last 15 years in a large Australian surgical series

Abstract: a male:female ratio of 1.9 : 1. Similarly sized tumours were identified in each time group [group 1 (1993-1997), 54.8 mm; group 2 (1998-2002), 52.0 mm; group 3 (2003-2007), 52.2 mm, P = 0.6].• Pathological stage II disease decreased from 18.1 to 11.1%, but stage III disease showed an increase from 13.9 to 21.5% over that time period ( P = 0.02).• The proportion of stage I and stage IV disease has remained relatively the same. There has been a statistically significant upward histological migration for the pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 15 publications
(15 reference statements)
3
22
2
1
Order By: Relevance
“…The rates determined in this study were 77.6% for clear cell RCC, 9% for papillary RCC, and 5.1% for chromophobe RCC. The histology types in this study showed patterns of frequency similar to those in other studies (7,9).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The rates determined in this study were 77.6% for clear cell RCC, 9% for papillary RCC, and 5.1% for chromophobe RCC. The histology types in this study showed patterns of frequency similar to those in other studies (7,9).…”
Section: Discussionsupporting
confidence: 89%
“…The rates of Fuhrman III and IV increased from 21.7% and 4.3% to 33% and 24.5%, comparable to the findings of Doeuk et al, who reported that the rates of Fuhrman III and IV increased from 17.6% and 6.8% to 30.8% and 8.3% (9). However, Pichler et al reported no change in Fuhrman grade in a 25-year period at a European center (8).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…15,16 In the context of such paradigm shift, PN, historically reserved for a tumor in a solitary kidney, bilateral Partial nephrectomy in T1b RCC renal tumors or renal function impairment, emerged as a viable alternative to RN. There is currently a strong body of literature supporting the use of PN over RN for T1a RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the downward stage migration in contemporary years (1,3), utilization Robot-assisted vs. Laparoscopic Partial Nephrectomy: utilization rates and perioperative outcomes _______________________________________________ rate of partial nephrectomy (PN) has increased significantly (4). PN has been demonstrated to provide equivalent oncologic control (5), improved renal function, a lower risk of cardiovascular disease, as well as improved overall survival (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%